A STUDY ON THE ABILITY OF THE THIRD YEAR STUDENTS OF ENGLISH STUDY PROGRAM FKIP UR IN WRITING SEQUENCE OF EVENTS OF REED’S MOVIE Yes Man - Siswandi, Ogi Siswandi Ogi; Azhar, Fadly Azhar Fadly (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study is to find out the third year students’ ability of English Study Program in writing sequence of events of Yes Man movie. This research focus on the accuracy in grammar, vocabulary mastery, the mechanics, arrange the form and style and ease of communication (fluency) based on the movie. Data were collected using writing test, particularly writing the sequence of events the movie. The research finding are as follows: firstly, the ability of the students based on three raters in writing plot of movie is 70.37 which is in Average to Good level. Second, the students’ average score based on three raters for Grammar aspect is 3.49, the average score for Mechanics is 3.54, in Vocabulary aspect the average score is 3.66, the students’ average score for Form is 3.31 and the last average score is Fluency, which is 3.39. The highest score obtained by the students is in Vocabulary aspect and the lowest score is in Form aspect.Keywords: Ability, Writing, Sequence of Events of Movie